Effectiveness of adherence to nutritional therapy in type 2 diabetics on hemodialysis - Salazar, Patricio; Anderson, Hazel (Revista Gregoriana de Ciencias de la Salud, 2025)
Type 2 diabetes is one of the leading causes of chronic kidney disease, and its treatment through hemodialysis requires strict adherence to nutritional therapy. This study evaluated anthropometric and biochemical parameters, as well as the degree of dietary adherence, in 87 patients with diabetic nephropathy undergoing hemodialysis in Ecuador. Serial measurements were conducted over a six-month period, and the DDFQ questionnaire was used to assess adherence to dietary and fluid restrictions. Significant sex-based differences were observed in waist, arm, and calf circumferences (p<0.001), as well as in phosphorus and potassium levels (p≤0.05). A total of 48% of patients showed a moderate deviation from the diet, and 34% a severe deviation. Significant correlations were found between the degree of dietary non-adherence and levels of albumin, creatinine, phosphorus, and potassium, suggesting that these biochemical markers may reflect nutritional adherence. No significant correlations were found between fluid restriction adherence and any other variables. These findings underscore the importance of enhancing nutritional education among hemodialysis patients and support the use of the DDFQ as a valuable tool for monitoring adherence to nutritional therapy.